A novel on-chip IM2 calibration method via LO pulse-width modulation for enhanced RF front-end linearity - Hussam AlShammary; Ali Muqaibel (Results in Engineering)
This paper first analyzes the impact of second-order intermodulation (IM2) distortion on the receiver (RX) chain and derives a compact analytical expression for the input-referred second-order intercept point (IIP2). Then, we propose a novel on-chip IM2 calibration technique that employs local oscillator (LO) pulse-width modulation to introduce an intentional mismatch, counteracting hardware-induced mismatches in passive mixers. The IM2 calibration method reduces the power of the generated distortion that severely impacts the linearity of direct-conversion as well as low intermediate-frequency (low-IF) Radio-Frequency (RF) receivers, and degrades the signal-to-noise-and-distortion ratio (SNDR). The proposed approach is implemented and verified in Taiwan Semiconductor Manufacturing Company (TSMC) 65 nm CMOS process demonstrating an improvement of up to 29 dB in differential-mode IM2 suppression while maintaining a compact form factor and incurring no additional power consumption. The calibration technique exhibits robust performance across temperature variations and can be seamlessly integrated into standard LO driver architectures. Compared to state-of-the-art IM2 calibration solutions, this work provides excellent linearity correction with minimal complexity, making it highly suitable for next-generation wireless communication systems.